1st International Experts’ Meeting on Agitation: Conclusions Regarding the Current and Ideal Management Paradigm of Agitation - Martínez-Raga, José; Amore, Mario; Di Sciascio, Guido; Florea, Radu Ioan; Garriga, Marina; Gonzalez, Gabriel; Kahl, Kai G.; Karlsson, Per-Axel; Kuhn, Jens; Margariti, Maria; Pacciardi, Bruno; Papageorgiou, Konstantinos; et al. (Frontiers in Psychiatry, 2018)
Agitation is a heterogeneous concept without a uniformly accepted definition, however, it is generally considered as a state of cognitive and motor hyperactivity characterized by excessive or inappropriate motor or verbal activity with marked emotional arousal. Not only the definition but also other aspects of agitated patients’ care are still unsolved and need consensus and improvement. To help the discussion about agitation among experts and improve the identification, management, and treatment of agitation, the 1st International Experts’ Meeting on Agitation was held in October 2016 in Madrid. It was attended by 20 experts from Europe and Latin America with broad experience in the clinical management of agitated patients. The present document summarizes the key conclusions of this meeting and highlights the need for an updated protocol of agitation management and treatment, the promotion of education and training among healthcare professionals to improve the care of these patients and the necessity to generate clinical data of agitated episodes.